Et rammeverk for makrotilsynsstresstester - Henrik Andersen; Karsten R. Gerdrup; Rønnaug M. Johansen; Tord Krogh (Norges Bank, 2019)
– We present a macroprudential stress testing framework. While traditional stress testing assesses the level of banks' capital adequacy relative to regulatory requirements through a hypothetical crisis, macroprudential stress testing assesses macroeconomic consequences of the impact of banks' adjustments to capital requirements. The outcome of such testing depends on the capital requirements and on banks' capital targets. The primary focus is not on whether or not banks "pass" the test, but on how macroprudential policy tools can prevent a deterioration of macroeconomic developments. Such analyses will be included in Norges Bank's decision basis for the countercyclical capital buffer. This framework was used to conduct the stress test in Financial Stability Report 2018.
hdl:11250/2587938
Keywords: C20; E30; R30; 330; Stresstest; DSGE-Modell; Finanzmarktaufsicht; Wirkungsanalyse; Norwegen